Co Framing analysis of media coverage on Gibran Rakabuming’s vice-presidency in Indonesia - riski, Riski; Zuly, Zuly Qodir; Suswanta (Faculty of Communications Science, Dr. Soetomo University, 2025)
In Indonesia’s contemporary political landscape, mass media plays a pivotal role in shaping public opinion through constructed narratives and representations. This study examined how two major online news outlets– CNN Indonesia and Detik.com, framed coverage of Gibran Rakabuming Raka as vice president of the Republic of Indonesia. Using a descriptive qualitative method and Entman’s (1993) framing theory, the research analyses articles published from January 2024 to June 2025. Data were collected from official websites and processed using NVivo 12 Plus to identify framing elements—problem definition, causal interpretation, moral evaluation, and treatment recommendation. Findings reveal that Detik.com frames Gibran positively, highlighting personal branding, electability, and grassroots engagement, while CNN Indonesia focuses on dynastic politics, democratic ethics, and legal controversies. These framing differences reflect each outlet's editorial stance and affirm the media's role in constructing political realities that influence public perception.